Đặc điểm địa hóa của các đá Lamprophyr tuổi Trias rìa khối nhô Kon Tum - Anh, Trần Tuấn; Hòa, Trần Trọng; Phượng, Ngô Thị; Dung, Phạm Thị; Vinh, Mai Kim (Vietnam Journal of Earth Sciences, 2008)
Geochemical significances of the Triassic lamprophyres at the margins of the Kon Tum Block